The Effect of Organizational Culture, Leader Behaviors, Job Satisfaction, and Justice On Organizational Commitment - Muhamad Suhardi; Syafaat Ariful Huda; Didi Mulyadi; Nada Nazopah (Yayasan Ahmar Cendekia Indonesia, 2020)
The purpose of this research is to find out information about the effect of organizational culture, leader behaviors, job satisfaction, and justice on organizational commitment. In this study, school is considered as an organization. The study was carried out at Islamic Junior High Schools in the Mataram City, NTB. The data for this survey reseach were collected by using quesionnaires distributed to fifty-nine teachers as the samples. The data were analyzed statistically using path analysis.The results of the analyses shows that: (1) organizational culture has a positive direct effect on organizational commitment, (2) leader behaviors have a positive direct effect on organizational commitment, (3) job satisfaction has a positive direct effect on organizational commitment, and (4) justice has a positive direct effect on organizational commitment.